2014
DOI: 10.4067/s0717-95022014000300036
|View full text |Cite
|
Sign up to set email alerts
|

Somatotipo de Atletas y Practicantes de Gimnasia Rítmica Prepubescentes y Postpubescentes

Abstract: RESUMEN: El objetivo fue identificar y comparar el somatotipo de atletas y practicantes de gimnasia rítmica de 7 a 25 años en Brasil, divididas en las siguientes categorías: diferentes niveles de competencia (internacional, nacional y regional) y practicantes de la modalidad en la fase prepubescente y postpubescente. El protocolo utilizado para la evaluación fue el somatotipo de Heath & Carter. Se realizó un estudio descriptivo, de lineación cuasi experimental, donde fueron evaluadas 125 atletas y practicantes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…The Latin American country Chile is highlighted as having produced the majority of relevant work [3][4][5]. This type of research is starting to emerge in Sustainability 2019, 11, 6224 2 of 12 other countries, but almost always, studies tend to refer to sportspeople from various specialities [6][7][8] or even to those who participate in artistic specialities [9]. In the majority of cases, these tend to be centred on older ages, with very few studies found using adolescents or younger children [10].…”
Section: Introductionmentioning
confidence: 99%
“…The Latin American country Chile is highlighted as having produced the majority of relevant work [3][4][5]. This type of research is starting to emerge in Sustainability 2019, 11, 6224 2 of 12 other countries, but almost always, studies tend to refer to sportspeople from various specialities [6][7][8] or even to those who participate in artistic specialities [9]. In the majority of cases, these tend to be centred on older ages, with very few studies found using adolescents or younger children [10].…”
Section: Introductionmentioning
confidence: 99%
“…The training in RG begins at the early age of 5-6 years and continues throughout childhood and adolescence [17][18][19]. The high-level athletes in RG achieve international status long before they become adults [20]. Thus, the late menarche is common among rhythmic gymnasts [4,6,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…El análisis del somatotipo de todo el grupo, mostro un predomino equilibrado de los componentes muscula-res y graso, aunque con una ligera ventaja del com-La Figura 1 muestra una somatocarta que describe las gimnastas catalogadas de acuerdo al biotipo de individual (puntos rojos) y el punto azul donde se encuentran ubicadas las deportistas evaluadas en este estudio según su media aritmética.Se obtuvo que en promedio (punto azul) tienen características de Endomorfo-Mesomorfo. Lo que nos señala una predominancia hacia la endomorfia en este tipo de deportistas de nivel universitario, las cuales se encuentran lejos del valor ideal para este deporte según el estudio deMenezes et al (2014), el somatotipo ideal de una gimnasta de elite debe ser Somatocarta de la muestra.…”
unclassified